Achieving “Adequate yearly progress” under “No child left behind”: problems and Obama administration’s solutions = Đạt “chuẩn tiến bộ hằng năm” trong giáo dục dưới đạo luật “no child left behind”: những vấn đề và giải pháp của chính quyền Obama - Nguyễn, Văn Sơn (2021)
During the country’s history of more than 200 years, the U.S. governments have been doing a lot to improve the education and support everyone to have the equal success chance. In such a context, many Acts and laws were born to fulfill the desires. No Child Left Behind (2001) is not exceptional. In this Act, Adequate Yearly Progress, the term appearing many times, was the measurement of how schools and districts perform academically with the goal that in 2014, every student would be proficient in Math and Reading. However, schools and states were confronted with a variety of problems in achieving it though well intended. As a result, the Obama administration has carried out many projects and enacted more policies to solve these issues. Therefore, this paper is conducted to investigate the problems in making AYP and the solutions offered by the administration as well as suggesting implications for Vietnamese education. Both primary sources and secondary sources were utilized to have a broader view, support the arguments and reach the important findings. Then, the researcher applied two main methods, namely, content analysis to analyze the texts through the words and concepts and secondary data analysis to dig deep into the existing dataset by other researchers to answer this thesis’s research questions. The findings indicated five main problems including unreachable goals, diversity in schools, different state policies, unreasonable requirements and inappropriate measurement. The Obama administration launched the Blueprint for Reform, which has yet to become a law and the ESEA waivers, which have been applied by more than 40 states and areas to deal with those issues. By understanding the problems and solutions, the researcher made several implications for education in Vietnam. They include setting a realistic goal, carefully considering the insiders’ background and ethnicity, utilizing various assessment tools and providing a precise mechanism of rewarding and punishing